A REVIEW OF PUBLISHED STUDIES ON ETHICS IN ACCOUNTING (Third Sector Social Economic Review, 2024)
Professionals are expected to comply with certain ethical principles and rules while performing their activities. Compliance with ethical principles is crucial in professions such as accounting, which have a significant impact on society. The study is a systematic literature review aimed at providing a database for future studies by examining applied studies on accounting professional ethics. The data used in the study comprises studies is included in the Web of Science database, Social Sciences Citation Index, and accounting journals indexed in TR Index in Turkey. The study has analysed 42 foreign and 29 national articles based on their subject, methodology, application, and results. The analysis has revealed that modern education methods are more effective, but traditional methods are more commonly used in ethics education in accounting. Although ethics education has included in university curricula for accounting, it is not at a sufficient level. In studies on professional members, it has found that professional members frequently experience ethical dilemmas. Ethical dilemmas have often caused by pressures from taxpayers and public authorities. Finally, the use of artificial intelligence in accounting is viewed positively. However, it is stated in the studies that this may reveal some ethical problems.
Keywords: Accounting Ethics; Ethics Education; Ethical Dilemma; Accounting Profession; Ethical Decision Making